2015
DOI: 10.1111/pai.12360
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus vs. cyclosporine eyedrops in severe cyclosporine‐resistant vernal keratoconjunctivitis: A randomized, comparative, double‐blind, crossover study

Abstract: Topical Tcr is very effective and safe in the short term for patients suffering from severe VKC resistant to topical Cyc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 22 publications
0
69
0
Order By: Relevance
“…A RCT comparing the effect of tacrolimus 0.1% vs CsA 2% showed that both drugs were effective in treating VKC without significant differences between the two. In a second RCT, CsA‐resistant VKC patients, treated with tacrolimus 0.1%, showed a significant improvement in clinical scores over CsA 1%. A recent trial comparing the effect of 0.1% topical tacrolimus alone or in combination with topical corticosteroids in refractory allergic ocular diseases also showed a potential steroid‐sparing effect .…”
Section: Resultsmentioning
confidence: 95%
“…A RCT comparing the effect of tacrolimus 0.1% vs CsA 2% showed that both drugs were effective in treating VKC without significant differences between the two. In a second RCT, CsA‐resistant VKC patients, treated with tacrolimus 0.1%, showed a significant improvement in clinical scores over CsA 1%. A recent trial comparing the effect of 0.1% topical tacrolimus alone or in combination with topical corticosteroids in refractory allergic ocular diseases also showed a potential steroid‐sparing effect .…”
Section: Resultsmentioning
confidence: 95%
“…Tacrolimus, derived from the bacterium Streptomyces tsukubaensis, like cyclosporine, is a calcineurin inhibitor in the immune mechanism but with a 100-fold-greater potency [12]. It suppresses Th2 lymphocyte activation, Th cell-mediated B cell proliferation, and the formation of cytokines.…”
mentioning
confidence: 99%
“…14 Pucci N et al, conducted studies using cyclosporine 1% and 2% concentrations15 in other study in 2015 they used 0.1% concentrations for patients who failed to respond to 1% Cyc eye drops. 16 Akpek EK et al, used 0.05% cyclosporine eye drops for treatment of severe steroid resistant vernal keratoconjunctivitis. 10…”
Section: Medicationsmentioning
confidence: 99%